Clustering of Y chromosome deletions in subinterval E of interval 6 supports the existence of an oligozoospermia critical region outside the DAZ gene. Issue 11 (November 1997) - Stuppia, L; Gatta, V; Mastroprimiano, G; Pompetti, F; Calabrese, G; Guanciali Franchi, P; Morizio, E; Mingarelli, R; Nicolai, M; Tenaglia, R; Improta, L; Sforza, V; et al.
Abstract : Y chromosome molecular analysis was performed using the STS-PCR technique in 50 patients with oligozoospermia. Microdeletions of interval 6 of the Y chromosome were detected in seven patients, in six of whom subinterval E was affected. All patients retained the RBM1 and DAZ genes, while in one deletion involved the SPGY gene. The size of the deletion was not apparently related to the severity of the disease. These results suggest the presence of an oligozoospermia critical region on the Y chromosome within subinterval E of interval 6.